Przekład – obiekt nostalgii? - Barbara Kaczyńska-Dudek (Między Oryginałem a Przekładem)
TRANSLATION – OBJECT OF NOSTALGIA? REACTIONS OF ADULT READERS TO POLEMICAL TRANSLATIONS OF CHILDREN’S LITERATURE